2019
DOI: 10.11604/pamj.2019.32.28.15464
|View full text |Cite
|
Sign up to set email alerts
|

Integrating immunization services into nutrition sites to improve immunization status of internally displaced persons� children living in Bentiu protection of civilian site, South Sudan

Abstract: Introduction The protracted war in South Sudan has led to severe humanitarian crisis with high level of malnutrition and disruption of the health systems with continuous displacement of the population and low immunization coverage predisposing the population to vaccine preventable diseases. The study aimed at evaluating the effect of integrating immunization services with already established nutrition services on immunization coverage in resource-constrained humanitarian response. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…The vaccination study by Oladeji et al 53 which evaluated the effect of integrating immunization services within nutrition services reported improvements in vaccination uptake and dose completion. The study showed that children in the two selected sites offering a combination of immunization and therapeutic food were about 27% and 45% less likely to miss vaccination compared to those vaccinated at primary healthcare centers with no food program (odds ratio, OR: 0.45; 95% CI:0.36-0.55, P < 0.05) and (OR: 0.27; 95% CI: 0.20 -0.35, P < 0.05) respectively.…”
Section: Disease Prevention Interventionsmentioning
confidence: 99%
See 4 more Smart Citations
“…The vaccination study by Oladeji et al 53 which evaluated the effect of integrating immunization services within nutrition services reported improvements in vaccination uptake and dose completion. The study showed that children in the two selected sites offering a combination of immunization and therapeutic food were about 27% and 45% less likely to miss vaccination compared to those vaccinated at primary healthcare centers with no food program (odds ratio, OR: 0.45; 95% CI:0.36-0.55, P < 0.05) and (OR: 0.27; 95% CI: 0.20 -0.35, P < 0.05) respectively.…”
Section: Disease Prevention Interventionsmentioning
confidence: 99%
“…The study showed that children in the two selected sites offering a combination of immunization and therapeutic food were about 27% and 45% less likely to miss vaccination compared to those vaccinated at primary healthcare centers with no food program (odds ratio, OR: 0.45; 95% CI:0.36-0.55, P < 0.05) and (OR: 0.27; 95% CI: 0.20 -0.35, P < 0.05) respectively. 53 The other two vaccination studies focused on specific diseases and aims: yellow fever vaccination administration and effectiveness 44 and IDP perception of cholera vaccination. 54 Both studies reported exceeding the 90% WHO vaccination coverage standard requirement; and the high coverage level was linked to the IDPs' high of level awareness about the disease severity.…”
Section: Disease Prevention Interventionsmentioning
confidence: 99%
See 3 more Smart Citations